The Fracture Pattern of Different Mandibular Over-Denture Designs - Ahmed M. Hussein (University of Mosul, College of Dentistry, 2008)
Aims: To evaluate the load at fracture for different mandibular over-dentures and the positions of thefracture area for these designs. Material and methods: Ten mandibular dentures were made, each oftwo designs. The first design consisted of acrylic resin over-denture supported by two dome-shaped 3mm mandibular canines copings, the second design consisted of two dome-shaped copings connectedwith a rigid metallic bar. The mean and standard deviation were calculated in addition to the analysis ofvariance which showed a significant difference at P < 0.05. Results: Showed that the over-denturesupported by two dome shaped mandibular canines were more fracture resistance than the over-denturesupported with the bar. The fracture position depends on the denture design. Conclusions: The resultsindicated that the denture made entirely of acrylic resin was much more stronger than the denture withless thickness due to the incorporation on metallic rigid bar.